Safety of gadolinium during pregnancy - Garcia-Bournissen, Facundo (College of Family Physicians of Canada, 2006)
QUESTION: A pregnant patient who underwent magnetic resonance imaging (MRI) because of an acute abdomen, was told that MRI contrast agents (ie, gadolinium-based contrast agents) are contraindicated during pregnancy. What is the risk to her baby? ANSWER: Current radiology practices and recommendations discourage the use of gadolinium-based contrast agents during pregnancy because their safety for the fetus has not yet been proven. In line, however, with the European Society of Radiology guidelines and based on the available evidence, gadolinium-based contrast agents appear to be safe in pregnancy. Gadolinium use should be considered when the diagnostic study is important for the health of the mother.